Estimating the credit risk score for non-bank stock exchange intermediaries in the eventuality of changeover to euro currency - laurențiu Paul Barangă; Iulian Panait (Financial Studies, 2018)
In this paper we build a system for determining the credit risk score and to estimate the probability of default for Romanian non-bank stock exchange intermediaries using principal component analysis applied on a selected set of financial and prudential indicators obtained from their financial statements and capital adequacy reports. Our approach is useful when dealing with non-listed undertakings, for which the probability of default cannot be derived from market prices. In addition, it can be replicated for the same type of companies in other jurisdictions and can be adapted to other type of non-bank financial intermediaries. The method could be especially useful for central counterparties. Regarding the eventuality of changeover to euro, this will have an insignificant impact on the financial credit risk score of Romanian non-bank intermediaries.
Keywords: G17; G23; 330; credit risk scoring; default probability; principal component analysis